Opioid Neonatal Abstinence Syndrome: An Overview. Issue 6 (29th December 2017) - Wexelblatt, Scott L.; McAllister, Jennifer M.; Nathan, Amy T.; Hall, Eric S.
Abstract : Opioid neonatal abstinence syndrome (NAS) refers to signs of withdrawal observed in infants experiencing intrauterine opioid exposures. Early identification of at‐risk infants allows for the prompt initiation of nonpharmacologic supportive care. When withdrawal symptoms are severe despite these interventions, pharmacologic therapy including opioid weaning is initiated. Consistency with standardized nonpharmacologic approaches as well as stringent weaning protocols are important in minimizing the length of stay and length of pharmacologic treatment for these vulnerable patients.